2021
DOI: 10.1007/s40267-021-00842-1
|View full text |Cite
|
Sign up to set email alerts
|

Systemic muscular weakness after botulinum toxin A administration: a review of the literature

Abstract: Objectives In this study we perform a review of the literature on systemic muscle weakness after administration of botulinum toxin A, to describe the factors that predispose patients to this adverse event and to suggest strategies for prevention. Methods Our search criteria included the terms "Botulinum toxin, Abobotulinum toxin, Dysport ® , Onabotulinum toxin, Botox ® , Incobotulinum toxin and Xeomin ® , muscle weakness, generalized muscle weakness and respiratory distress." Statistical analysis was completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 68 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Most authors agree that botulism toxicity generally results from the use of an unlicensed botulinum toxin product, or an overdose [25,30]. A systematic review of 63 cases of the systemic muscle weakness related to botulism found that, on average, the doses in affected patients were over three times the recommended dose for the preparation being used [31]. The same review suggested the most practical solution for reducing the risk of botulism is to use botulinum toxin-A preparations that are approved by the United States Food and Drug Administration (FDA) at recommended doses [31].…”
Section: Adverse Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most authors agree that botulism toxicity generally results from the use of an unlicensed botulinum toxin product, or an overdose [25,30]. A systematic review of 63 cases of the systemic muscle weakness related to botulism found that, on average, the doses in affected patients were over three times the recommended dose for the preparation being used [31]. The same review suggested the most practical solution for reducing the risk of botulism is to use botulinum toxin-A preparations that are approved by the United States Food and Drug Administration (FDA) at recommended doses [31].…”
Section: Adverse Effectsmentioning
confidence: 99%
“…A systematic review of 63 cases of the systemic muscle weakness related to botulism found that, on average, the doses in affected patients were over three times the recommended dose for the preparation being used [31]. The same review suggested the most practical solution for reducing the risk of botulism is to use botulinum toxin-A preparations that are approved by the United States Food and Drug Administration (FDA) at recommended doses [31]. Regarding localized decreases in muscle strength, authors noted that these decreases did not result in functional impairment and patients were overall satisfied with the outcomes of their treatments [2,3,12].…”
Section: Adverse Effectsmentioning
confidence: 99%
See 1 more Smart Citation